Risk factors for the development of systemic lupus erythematosus (sle) in asians: a research case-control - Tashinova Laylo; Khamraeva Nasiba; Mambetova Lobar; Khasanov Farrukh; Ibragimov Khasan (BIO Web of Conferences, 2023)
The study aimed to assess the nature of injuries and determine the risk factors for accumulated injuries in a group of patients with SLE. Materials and methods. A retrospective review of the map and medical history in the therapeutic department of the SamMI clinic was conducted on a group of 75 patients with SLE. The collected data included (1) age at the time of diagnosis, (2) gender, (3) heredity, (4) manifestations of the disease at diagnosis, (5) laboratory data, including a general blood test, complement levels (C3, C4). Results. 225 people were included in this study: 75 in the main group (patients with asthma) and 150 in the control group (healthy). Of the participants in the study, 44% were women and 56% were men; both groups were the same gender. The damage from the disease was significantly associated with a younger age at the time of diagnosis (P = 0.03), the presence of neuropsychiatric manifestations at any stage of the disease (P <0.01), a large number of lesions of the main organs (P <0.01), a large number of lesions. outbreaks of lupus (P <0.01) and a greater number of episodes of serious infection (P = 0.02). Conclusions. This study presents a picture of accumulated damage in a group of 59 Asian patients with SLE. This shows that the presence of neuropsychiatric manifestations is a significant risk factor for damage. Other likely risk factors for the disease include younger age at the time of diagnosis, a greater number of lesions of the main organs, a greater number of exacerbations and serious infections.